Thermoregulatory and perceptual responses of lean and obese fit and unfit girls exercising in the heat - Carolina de Ávila Rodrigues; Gabriela Tomedi Leites; Flavia Meyer (Brazilian Society of Pediatrics, 2020)
Objective: To verify the thermoregulatory and perceptual responses of obese and lean girls, either fit or unfit, exercising in the heat at a similar rate of metabolic heat production per unit body mass. Methods: A total of 34 pubescent girls were allocated in four groups: 12 obese fit, 9 obese unfit, 5 lean fit, and 8 lean unfit. The obese groups (13.2 ± 1.4 years, 40.5% ± 5.8% fat by DXA) differed in their aerobic fitness (V˙O2peak 76.0 ± 8.1 vs. 56.6 ± 5.8 mL.kg muscle mass‐1.min−1), as well as the lean groups (13.1 ± 1.6 years, 24.0% ± 4.8% fat) (V˙O2peak 74.5 ± 2.9 vs. 56.2 ± 5.0 mL.kg muscle mass−1 min−1). Girls cycled two bouts of 25 min with a 10 min rest in between, at ∼5.4 W.kg−1 in the heat (36 °C and 40% relative humidity) and they were kept euhydrated. Rectal and skin temperatures and heart rate were measured every 5 min. Perceptual responses were evaluated throughout the exercise. Results: Initial rectal temperature was higher in the obese subjects compared to the lean subjects (37.5 ± 0.3 and 37.2 ± 0.3 °C). No difference was observed among the girls whom were obese (eight fit or unfit) and lean (also fit or unfit) throughout the exercise in rectal temperature (37.6 ± 0.2, 37.5 ± 0.3, 37.5 ± 0.3, 37.4 ± 0.3 °C, respectively), skin temperature (34.8 ± 0.8, 35.1 ± 1.0, 34.4 ± 0.9, 35.2 ± 0.9 °C), and heart rate (128 ± 18; 118 ± 12, 130 ± 16, 119 ± 16 beats min−1). No differences were observed in perceptual responses among groups. Conclusion: Regardless of the adiposity or aerobic fitness, pubescent girls had similar thermoregulatory and perceptual responses while cycling in the heat at similar metabolic heat production. Resumo: Objetivo: Verificar as respostas termorregulatórias e perceptivas de meninas obesas e magras, com alta e baixa aptidão aeróbica, exercitando‐se no calor com produção metabólica de calor similar por massa corporal. Métodos: Um total de 34 meninas púberes foram alocadas em quatro grupos: 12 obesas com alta aptidão aeróbica, 9 obesas com baixa aptidão aeróbica, 5 magras com alta aptidão aeróbica e 8 magras com baixa aptidão aeróbica. Os grupos obesos (13,2 ± 1,4 anos, 40,5% ± 5,8% de gordura por DXA) diferiram em sua aptidão aeróbica (V˙O2peak 76,0 ± 8,1 vs. 56,6 ± 5,8 mL.kg de massa muscular−1.min−1), bem como os grupos magros (13,1 ± 1,6 anos, 24,0% ± 4,8% de gordura) (V˙O2peak 74,5 ± 2,9 vs. 56,2 ± 5,0 mL.kg de massa muscular−1min−1). As meninas pedalaram duas sessões de 25 minutos com descanso de 10 minutos entre as sessões, a ∼5,4 W.kg−1 no calor (36∘C e 40% de umidade relativa) e foram mantidas hidratadas. As temperaturas retal e cutânea e a frequência cardíaca foram medidas a cada 5 minutos. As respostas perceptivas foram avaliadas durante o exercício. Resultados: A temperatura retal inicial foi maior nas meninas obesas em comparação com as magras (37,5 ± 0,3 e 37,2 ± 0,3 °C). Não houve diferença entre as meninas obesas (com alta aptidão aeróbica ou não) e magras (também com alta aptidão aeróbica ou não) durante todo o exercício em relação à temperatura retal (37,6 ± 0,2; 37,5 ± 0,3; 37,5 ± 0,3; 37,4 ± 0,3 °C; respectivamente), temperatura da pele (34,8 ± 0,8; 35,1 ± 1,0; 34,4 ± 0,9; 35,2 ± 0,9 °C), e frequência cardíaca (128 ± 18; 118 ± 12, 130 ± 16, 119 ± 16 batimentos.min−1). Não foram observadas diferenças nas respostas perceptivas entre os grupos. Conclusão: Independentemente da adiposidade ou do condicionamento aeróbico, as meninas púberes tiveram respostas termorregulatórias e perceptivas semelhantes, enquanto pedalavam no calor com uma produção metabólica de calor similar.